Systematic Rehabilitation Techniques and Dynamic Analysis of Bridge Deck System with Concrete-Filled Steel Tube Arches - Jie Cai; Zikang Zou; Zhipeng Wang (Buildings)
Due to prolonged heavy traffic, the Wuhan Changfeng Bridge has experienced extensive cracking in its main girder structure. Of the bridge’s 60 crossbeams, 51 (85%) have developed cracks, while the deck pavement over the steel beams has accumulated a total of 648.8 m of transverse cracks. Additionally, two T-beams exhibit structural vertical cracks of 0.3 mm at the mid-span, exceeding the maximum allowable width of 0.2 mm. This recurrent pavement damage not only compromises driving safety and comfort but also increases maintenance costs. To address these issues, this paper proposes a systematic upgrade plan for the bridge deck system. The plan involves welding additional high transverse beams onto the existing steel transverse beams, removing the original deck slab and replacing it entirely with an orthotropic steel deck. Additionally, two new steel longitudinal beams will be installed. The original simply supported concrete longitudinal beams in the deck will be transformed into an integrally connected continuous steel structure deck system. Using Midas/Civil finite element software, 3D models of Changfeng Bridge, pre and post renovation, were created to analyze the overall dynamic characteristics under five loading scenarios. The ambient vibration test and vehicle field test were conducted to measure the bridge’s natural frequency and impact factor, verifying the dynamic performance and driving comfort of the bridge after the upgrade. The results indicate that the retrofitted bridge experienced a 19.9% increase in overall stiffness. The dynamic performance of the bridge structure was significantly enhanced, and the most notable improvement was observed in dynamic stress, which decreased by 19.4% to 76.9%. Additionally, the steel deck reduced the bridge’s dead load, and the driving comfort on the bridge deck improved.